2015
DOI: 10.1111/ipd.12219
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual administration of atropine eyedrops in children with excessive drooling – a pilot study

Abstract: BackgroundDrooling can be a severe disability and have high impact on daily life. Reversible treatment is preferable.AimTo analyse whether sublingual administration of atropine eyedrops is a useful reversible treatment option for severe drooling in children with disabilities.DesignThe study had a prospective, single‐system research design. The participants served as their own controls. The study period was 3 weeks without treatment, 4 weeks with atropine eyedrop solution 10 mg/mL one drop a day followed by 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 36 publications
3
37
1
Order By: Relevance
“…Another pilot study about children with sialorrhea (n = 11) with various underlying disorders (including cerebral palsy, epilepsy, and autism) showed a significant reduction in salivation after sublingual administration of atropine eye drops 1‐2× a day, by weighing dental cotton wool rolls and measurement on a visual analogue scale or VAS with the parents). No irreversible adverse reactions were noted, xerostomia occurred in 3 children and some parents reported difficulties with the administration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another pilot study about children with sialorrhea (n = 11) with various underlying disorders (including cerebral palsy, epilepsy, and autism) showed a significant reduction in salivation after sublingual administration of atropine eye drops 1‐2× a day, by weighing dental cotton wool rolls and measurement on a visual analogue scale or VAS with the parents). No irreversible adverse reactions were noted, xerostomia occurred in 3 children and some parents reported difficulties with the administration.…”
Section: Resultsmentioning
confidence: 99%
“…Possible side effects in the reviewed literature are the occurrence of xerostomia at higher dosages: with one patient with CIS this occurred with three drops and in 3 out of 11 children studied by Norderyd taking only 1 to 2 doses per day. The unpleasant taste and at times, the too short duration of action with reoccurrence of salivation in the early morning, which on its turn can be managed by the “top‐up method” .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Negatively affecting social relationships, it is a factor that reduces a person's selfrespect. 3 Sialorrhea may be due to neuromuscular, sensorial, or anatomic disorders, while the most common cause is neuromuscular dysfunction. 4 Medical, surgical as well as behavioral treatment methods may be applied to reduce the secretions.…”
Section: Introductionmentioning
confidence: 99%
“…5 Biofeedback and acupuncture methods are among the experimental treatment methods. 3 According to 2012 Cochrane data, there is insufficient evidence of success of treatments applied for oral secretions in pediatric patients monitored for cerebral palsy. 3 In recent years, some publications have demonstrated that sublingual atropine eye drops are effective in reducing secretions in adults and children.…”
Section: Introductionmentioning
confidence: 99%